The effect of synthesized cartilage tissue from human adipose-derived mesenchymal stem cells in orthopedic spine surgery in patients with osteoarthritis - Weijie, Tang; Xinhua, Guan; Jingqi, Han; XiLing, Yin; Zuoji, Feng (Cellular and Molecular Biology, 2021)
Osteoarthritis is a joint disease that causes degeneration of articular cartilage and involvement of subcutaneous bone and inflammation of surrounding tissues. It can affect any joints, but the most common joints are the joints of the hands, feet, knees, thighs, and spine. Osteoarthritis patients need surgery in acute cases. The use of methods that increase the efficiency of this surgery has always been considered by researchers and surgeons. For this purpose, in the current study, the effect of synthesized cartilage tissue from human adipose-derived mesenchymal stem cells was considered in orthopedic spine surgery in patients with osteoarthritis. Thirty patients over the age of 60 who had acute spinal osteoarthritis and required surgery were selected. The pellet culture system of human adipose-derive mesenchymal stem cells of each patient was used to construct cartilage tissue. For 15 of them, in addition to implants, cartilage grafts were transplanted during surgery. All patients were monitored by the Oswestry Disability Index questionnaire, for one year. In general, the results showed that over time, patients with transplanted cartilage tissue and implants were in a better condition than patients who underwent only implant surgery.